Designing a Cloud-Based Smart-EduVerse Management System forPrescriptive Quality Governance in Higher Education: AMixed-Methods Study - Rochmawati Rochmawati; Anik Nur Handayani; Tran Thi Hao; Soubin Sisavath (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2026)
The purpose of this study is to develop a Cloud-Based Smart-EduVerse Management System (S-EMS) architecture as a digital quality mapping framework designed to strengthen Sustainable Competitive Advantage (SCA) in Indonesian State Universities with Legal Entity (PTNBH) status amid the VUCA era. This study employed a mixed-methods approach using a concurrent embedded design with qualitative dominance. The research involved 22 PTNBHs, with qualitative data collected through in-depth interviews, observations, and document analysis, while quantitative data were obtained through questionnaires. Both datasets were integrated during the interpretation stage using constant comparative analysis and descriptive statistics to formulate the system architecture and governance requirements. The results indicate that S-EMS consists of three cloud-based functional layers: (1) a prescriptive datamapping layer integrating institutional quality indicators, (2) a cloud-hosted knowledge asset management module for organizing human and intellectual capital, and (3) an adaptive governance dashboard supporting real-time cross-campus decision-making. Quantitative findings show that 19 of the 22 universities (86.4%) have integrated digital infrastructure, while strategic collaboration and adaptive quality assurance practices were implemented across nearly all participating institutions. These findings demonstrate that the proposed architecture reduces data fragmentation, improves interoperability, and supports evidence-based governance, facilitating a transition from compliance-based to impact-based institutional management. This study contributes a validated cloud-based Smart-EduVerse Management System (S-EMS) framework integrating digital quality mapping, knowledge asset management,and prescriptive governance to strengthen sustainable competitive advantage in higher education.